Impact of July 2004 high-intensity rain on Hilepani-Jayaramghat-Diktel Environment-Friendly Road in East Nepal - Dhital, Megh Raj (Journal of Nepal Geological Society, 2006)
The high-intensity rain of 5-13 July 2004 activated numerous landslides, gullies, and debris flows in the watershed of the Dudh Koshi River in east Nepal. As a result, the Hilepani- Jayaramghat- Diktel Environment-Friendly Road was devastated. Apart from the rainfall, geological, geomorphic, land use, and road construction practices were other important factors leading to the disaster. Most of the damage was concentrated on concave slopes, whereas the ridges and convex slopes were relatively safe. The entire alignment was devoid of any breast or retaining walls necessary to protect the high, steep, and bare soil cut slopes, and it resulted in extensive cut slope failures. Similarly, side and cross drains were almost nonexistent. As a result, severe damage was seen at almost every gully crossing. There were very few gully protection structures (viz. check dams) and, like the retaining walls constructed below the road, they also suffered from poor construction quality and failed due to weak foundation and inadequate keying practices. Some of the most awkward structures were the loops founded on unstable slopes with high (up to 15 m) and robust gabion walls at the bends, and deep box cuts above them. In these circumstances, the concentrated runoff and subsequent debris flow from the box cut devastated the entire hairpin bend.